"Functional communication between IP3R and STIM2 at subthreshold stimuli is a critical checkpoint for initiation of SOCE". (June 2022) - Humer, Christina; Romanin, Christoph
Highlights: Ca 2+ signaling drives versatile cellular processes, being for instance sensitive to the strength of activating stimuli. Cells rely on the concerted interplay of a series of proteins to control the onset and duration of increases in intracellular Ca 2+ and to avoid erroneous channel activation. STIM2 is sensitive to low levels of ER-Ca 2+ store depletion and is a key component in a checkpoint system controlling the activation of the STIM1-Orai1 CRAC channel complex. The function of STIM2 is highly dependent on IP3R proteins yet in the absence of direct interactions. Abstract: The family of stromal interaction molecules (STIMs), comprising the homologs STIM1 and STIM2 with their different isoforms, has an intricate role in cellular calcium (Ca 2+ ) homeostasis and signal transduction. While this is predominantly accomplished in concert with plasma membrane Orai proteins, STIM1 and STIM2 show essential functional differences, as was recently further elucidated by Ahmad et al. [1] .